Penerapan User Experience pada Aplikasi Pendaftaran Online RSUD Umar Wirahadikusumah Sumedang - Soffiah Ai Nurjanah; Dwi Yuniarto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
This study aims to evaluate the user experience of the Online Registration application of Umar Wirahadikusumah Sumedang Hospital using the User Experience Questionnaire (UEQ) method. The evaluation was carried out on six aspects, namely attractiveness, clarity, efficiency, accuracy, stimulation and novelty, involving 30 application user respondents. The results showed that the Online Registration application of Umar Wirahadikusumah Sumedang Hospital received a Bad score on the Attractiveness aspect with a mean value of 0.42, the Clarity aspect received a Bad score with a mean value of 0.43, the Efficiency aspect received a Bad score with a mean value of 0.44, the Dependability aspect received a Bad score with a mean value of 0.48, the Stimulation aspect received a Bad score with a mean value of 0.35, and the Novelty aspect received a Below Average score with a mean value of 0.20. The results show that the application still needs to require improvements in various aspects to improve the quality of the user experience. Some recommendations that can be considered to provide better services include improving the interface that attracts user attention, simplifying the application flow, optimizing application performance so that it can be used efficiently, and adding some more innovative features.